2011
DOI: 10.1143/jjap.50.09nd14
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Piezoelectric Power Generation of Multilayered Poly(vinylidene fluoride) under High Mechanical Strain

Abstract: Relativistically the corrected transition potential of quark to quark-quark-antiquark is derived. With the input of the quark wave function and the quark-gluon coupling constant determined in a chiral quark soliton model, this transition potential is used to obtain the deuteron binding energy in the resonating group method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…15 and an early study indicated in Ref. 23, respectively. From the obtained results, the theoretically calculated force of the 30-multilayered PLLA film is more than 10 times larger than that of the single-layered PVDF film.…”
Section: Evaluation Of Vibration In the Edge Facementioning
confidence: 92%
See 1 more Smart Citation
“…15 and an early study indicated in Ref. 23, respectively. From the obtained results, the theoretically calculated force of the 30-multilayered PLLA film is more than 10 times larger than that of the single-layered PVDF film.…”
Section: Evaluation Of Vibration In the Edge Facementioning
confidence: 92%
“…Here, we derive and calculate the excitation force theoretically. 8,13,15,[21][22][23] The excitation force of the edge face F is expressed by deriving a d-type piezoelectric equation as…”
Section: Evaluation Of Vibration In the Edge Facementioning
confidence: 99%
“…Moreover, by substituting a H atom by a F atom in one of the four VDF monomers in the cell, a 75/25 mol% P(VDF-TrFE) was constructed, and the e 33 for P(VDF-TrFE) was calculated as −0.211 C m −2 . In addition to the above studies, theoretical calculations can also be obtained for shear piezoelectricity, [230] the effect of large elastic strain on piezoelectric properties, [231] the piezoelectric properties of PVDF-based composite piezoelectric materials, [232,233] and the effect of processing conditions on piezoelectric properties. [234]…”
Section: Theoretical Calculations and Numerical Analysis Of Piezoelec...mentioning
confidence: 99%
“…10). 24,25) The surplus electric power from the photoelectric cell was stored in a capacitor, thus eliminating the need for batteries.…”
Section: Applicationsmentioning
confidence: 99%